ANALISIS UJI BENDING KOMPOSIT SERAT DAUN NANAS DAN PARTIKEL PASIR BESI DENGAN METODE VACUUM BAGGING - Fikri, Moh Afif Fikri; Setiawan, Ferry; Sofiyan, Edy (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2024)
This study aims to determine the effect of variations in the size of the pineapple leaf fiber frame on the flexural strength and modulus of elasticity of pineapple leaf fiber composites and iron sand. Variations in the size of the pineapple leaf fiber frame used are 5%, 10%, and 15%. The method of making composite specimens uses the vacuum bagging method. Flexural strength testing was carried out using the three point bending method. The results showed that the variation of pineapple leaf fiber frame size had a significant effect on the flexural strength and modulus of elasticity of pineapple leaf fiber and iron sand composites. Test specimens with 15% frame size variation had a maximum flexural strength of 76.9 MPa and a maximum elastic modulus of 639.76 MPa. Test specimens with 10% frame size variation had an average flexural strength of 53.7 MPa and an average elastic modulus of 192.74 MPa. Test specimens with 5% frame size variation had an average flexural strength of 44.3 MPa and an average elastic modulus of 164.04 MPa. The increase in flexural strength and modulus of elasticity of pineapple leaf fiber and iron sand composites with 15% frame size variation is due to several factors, namely: First, the increase in the number of pineapple leaf fibers in the composite. The greater the number of pineapple leaf fibers, the greater the tensile strength and modulus of elasticity of the composite. Second, the increase in composite density. The larger the size of the pineapple leaf fiber frame, the smaller the cavity formed in the composite. Cavities in the composite can reduce the tensile strength and elastic modulus of the composite. Based on the results of this study, it can be concluded that the use of 15% frame size variation as pineapple leaf fiber reinforcement can be used to make a matrix that can increase flexural strength and elastic modulus.